If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -5 = 3t + 6 Reorder the terms: -5 + 6t = 3t + 6 Reorder the terms: -5 + 6t = 6 + 3t Solving -5 + 6t = 6 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -5 + 6t + -3t = 6 + 3t + -3t Combine like terms: 6t + -3t = 3t -5 + 3t = 6 + 3t + -3t Combine like terms: 3t + -3t = 0 -5 + 3t = 6 + 0 -5 + 3t = 6 Add '5' to each side of the equation. -5 + 5 + 3t = 6 + 5 Combine like terms: -5 + 5 = 0 0 + 3t = 6 + 5 3t = 6 + 5 Combine like terms: 6 + 5 = 11 3t = 11 Divide each side by '3'. t = 3.666666667 Simplifying t = 3.666666667
| (2u+3)(5+u)=0 | | 4x+2=-x+12 | | .70x+.35(120)=.35(96) | | 2z=i(2+9i) | | 2x^214=102 | | .25x+.15y=19 | | G=um | | P(X)=200-0.2x | | .4x+x=1250 | | (x-1)*dy=2x^3y*dx | | 2(x+3)-4=12 | | 12+4*x^3+12*x^2+123*x=0 | | 100-p=.8p-8 | | 4*x^3+12*x^2+123*x=0 | | 5x+7=43-4x | | a*x^2=2 | | 3-3*6-2x=0 | | 7y-2=4y+25 | | -2.5=3n-1 | | 6w^2+24w=0 | | x^2+6x+21=-4x | | 5xSquare-10=0 | | 3(e+3f)= | | (6/3+4)= | | x^2-16x+100=36 | | 10.6x+58.54=-9.4x+58 | | X^5-x^4+x^3-x^2= | | 10x+197=2x-187 | | 3x-5y-58=0 | | (5t-3)=3(t+1)+3 | | 3ab^2+6a= | | 7(r)=3.14r^2 |